Local identity as a determining factor of Cittaslow city development based on the example of Lidzbark Warmiński - Markowski, Łukasz (Tożsamość lokalna jako determinanta rozwoju miasta Cittaslow na przykładzie Lidzbarka Warmińskiego, 2019)
The article deals with the role and significance of local identity in city development. The Cittaslow movement is a concept promoting city development based on a strong bond between the inhabitants and the given area, Lidzbark Warmiński being one of the first Polish cities to join the network. However, the implementation of the Cittaslow model may be more difficult in the region of Warmia and Mazury, due to historical factors, among others. These circumstances prompted conducting a survey among the inhabitants of Lidzbark Warmiński, the main aim of which was to determine whether, in their opinion, participation in the Cittaslow network influenced their subjective sense of local identity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 79-91
Keywords: local identity; city development; Cittaslow; Lidzbark Warmiński; toższamość lokalna; rozwój miasta